Analisis Peran Document Control Department QA/QC Pada PT. STB - sudanto sudanto; eka Aprianna (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2024)
PT STB is a company that has the foundation on which PT was built. STB is safety, quality, commitment and customer satisfaction. The purpose of this research is to analyze the role of a document control person at PT. STB. This research uses a qualitative descriptive approach, namely presenting the results of the analysis found regarding the role of document control at PT. STB. Data collection using interviews, direct observation and documentation of respondents and data sources analyzed. The results of the analysis show that the role of Document Control at PT. STB consists of creating a summary report, creating and inputting a master list report, compiling a total nesting data document, scanning, copying and renaming the report, filing (filling) into a Gobi folder, printing and photocopying the report, laminating welder identification pass, photograph the hardness test data, stick pict art paper on the data logger print out and check the client's signature. From the results of this research, it is hoped that it can provide a better understanding of the importance of a document control system and provide recommendations for improving document management in the future.